Montreal's environmental justice problem with respect to the urban heat island phenomenon - Fan, Jia Yi; Sengupta, Raja (The Canadian geographer, 2022)
Due to climate change, heat events in Canada have become more extreme in intensity and frequency and will continue to do so according to the Intergovernmental Panel on Climate Change's global predictions. Environmental justice research has indicated that extreme heat exposure disproportionally affects socio‐economically disadvantaged populations in cities. The objective of this research was to determine whether such a phenomenon exists in Montreal, Canada. Temperature data were obtained through in‐situ sensors and governmental weather stations, while census data were retrieved from Statistics Canada through the Census mapper. Correlation tests were run between temperature and five demographic and socio‐economic variables measured inside a 500 m buffer around the temperature sensors. The variables included Indigenous Peoples (IND), people of 65 years old and over (Over 65), people between 25 and 64 years old without a high school degree (No HS), and low‐income (LI). A positive correlation was found for LI and No HS (p < 0.05). A regression test performed with interpolated temperature and the demographic and socio‐economic variables across the study area revealed no significant correlation due to spatial heterogeneity. Le problème de justice environnementale à Montréal en ce qui concerne le phénomène d’îlots de chaleur urbains En raison des changements climatiques, les canicules au Canada sont devenues plus extrêmes en intensité et en fréquence et elles continueront de l’être selon les prévisions mondiales du Groupe d'experts intergouvernemental sur l'évolution du climat. Les recherches sur la justice environnementale ont démontré que l'exposition à la chaleur extrême affecte de manière disproportionnée les populations désavantagées sur le plan socio‐économique dans les zones urbaines. L'objectif de la présente recherche consistait à déterminer si un tel phénomène existe à Montréal, au Canada. Les données sur la température ont été obtenues au moyen de capteurs in‐situ et de stations météorologiques gouvernementales alors que les données du recensement de Statistique Canada ont été extraites au moyen du Census mapper. Des tests de corrélation ont été effectués entre la température et cinq variables démographiques et socio‐économiques mesurées dans une zone tampon de 500 mètres autour des capteurs de température. Les variables incluaient les Autochtones (AUT), les personnes âgées de 65 ans et plus (Plus de 65), les personnes âgées de 25 à 64 ans sans diplôme d'études secondaires (Pas d'ÉS) et à faible revenu (FR). Une corrélation positive a été trouvée pour FR et Pas d'ÉS (p < 0.05). Toutefois, un test de régression effectué avec la température interpolée et les variables démographiques et socio‐économiques à travers la zone étudiée n'a révélé aucune corrélation importante en raison de l'hétérogénéité spatiale. Key Messages Low‐income individuals and those without a high school degree were affected by environmental injustice related to the urban heat island effect at the 500 m buffer level. Spatial heterogeneity across the Island of Montreal caused a lack of correlation between the remaining demographic and socio‐economic variables. Additional work is required to understand the contribution of urban social processes such as gentrification to the nature of this environmental injustice.